The Development of Conceptual Design of Nurse assistance Robot’s Exterior with Ergonomic Approach - Dwinandana, Tubagus Ahmad; Kasih, Tota Pirdo; Puji, Muhammad Nurul (Fakultas Teknik Universitas Pancasila, 2024)
Nurses are human resources who have an important role in medical installations, especially hospitals. Nurses have various tasks such as assisting doctors in examining, treating and serving patients, and other tasks such as administration. With these various tasks, physical and mental fatigue often occurs in nurses. To reduce the workload, robots have been used in hospitals around the world, especially in hospitals in Indonesia. This research aims to produce an initial concept for the exterior design of a nursing assistant robot using an ergonomics approach. The research methodology uses product design and development framework, especially in conceptual design process which start from customer needs identification to design iteration. From the research it can be concluded that determining robot dimensions is based on anthropometric standards, user posture, hardware size, and so on. The main consideration in determining the size of the robot is the reach of the hand to pick up and store items, the range of the eye to see the interactive display screen.